Pengaruh Tingkat Utang dan Gender Direktur Perempuan terhadap Profitabilitas Perusahaan Sektor Food & Beverage yang Terdaftar di Bursa Efek Indonesia Periode 2022-2024 - Nurul Sapna Joetry; Fitri Yunina; Hendri Mauliansyah (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze the effect of debt level and female director gender on the profitability of companies in the Food & Beverage sector listed on the Indonesia Stock Exchange (IDX) during the 2022–2024 period. Profitability is measured using Return on Assets (ROA), the debt level is proxied by the Debt to Equity Ratio (DER), while female director gender is measured using a dummy variable. This study employs a quantitative method with a panel data approach involving 20 companies, resulting in a total of 60 observations. Panel data regression is used as the analytical technique. The results indicate that the debt level and female director gender simultaneously affect corporate profitability. Partially, each variable also shows a significant effect on profitability. These findings indicate that optimal debt structure management and the presence of female directors on the board play an important role in improving corporate financial performance.